Soft target hardening: protecting people from attack - Hesterman, Jennifer L. (Routledge, Taylor & Francis Group, 2019)
Soft targets -- The psychology of soft target and our unique vulnerability -- International terror groups : propensity and ability to mount soft target attacks -- Domestic terrorism and the homegrown threat -- Soft target threat assessment : schools, churches, and hospitals -- Soft target threat assessment : malls, sporting events, and recreational venues -- New tactics and emergent threats -- Soft target hardening and the human element -- Deterring and mitigating attack -- Takeaways about soft target hardening